Clumped-isotope thermometry of magnesium carbonates in ultramafic rocks - García del Real, Pablo; Kluge, Tobias (Geochimica et cosmochimica acta, 2016)
Magnesium carbonate minerals produced by reaction of H2O-CO2 with ultramafic rocks occur in a wide range of paragenetic and tectonic settings and can thus provide insights into a variety of geologic processes, including (1) deposition of ore-grade, massive-vein cryptocrystalline magnesite; (2) formation of hydrous magnesium carbonates in weathering environments; and (3) metamorphic carbonate alteration of ultramafic rocks. However, the application of traditional geochemical and isotopic methods to infer temperatures of mineralization, the nature of mineralizing fluids, and the mechanisms controlling the transformation of dissolved CO2 into magnesium carbonates in these settings is difficult because the fluids are usually not preserved. Clumped-isotope compositions of magnesium carbonates provide a means to determine primary mineralization or (re)equilibration temperature, which permits the reconstruction of geologic processes that govern magnesium carbonate formation. We first provide an evaluation of the acid fractionation correction for magnesium carbonates using synthetic magnesite and hydromagnesite, along with natural metamorphic magnesite and low-temperature hydromagnesite precipitated within a mine adit. We show that the acid fractionation correction for magnesium carbonates is virtually indistinguishable from other carbonate acid fractionation corrections given current mass spectrometer resolution and error. In addition, we employ carbonate clumped-isotope thermometry on natural magnesium carbonates from various geologic environments and tectonic settings. Cryptocrystalline magnesite vein deposits from California (Red Mountain magnesite mine), Austria (Kraubath locality), Turkey (Tutluca mine, Eskişehir district) and Iran (Derakht-Senjed deposit) exhibit broadly uniform Δ47 compositions that yield apparent clumped-isotope temperatures that average 23.7 ± 5.0 °C. Based on oxygen isotope thermometry, these clumped-isotope temperatures suggest mineralization at shallow crustal depths in the presence of meteoric water. Hydrous magnesium carbonates from a 400-km latitudinal transect along the serpentinized-peridotite bodies of the California Coast Ranges record clumped-isotope temperatures between 14.2 and 22.7 ± 2.8 °C, in agreement with historical maximum temperatures during the rainy season for California. Talc-carbonate alteration of ultramafic rocks in Greenland (Isua Supracrustal Belt) and Vermont (Ludlow) yields clumped-isotope alteration temperatures of magnesite and dolomite between 326 and 490 °C, broadly consistent with paragenesis and thermodynamic analysis for CO2 metasomatism of ultramafic rocks. These metamorphic carbonates extend the applicability of clumped-isotope thermometry to high-temperature magnesium carbonate systems and indicate equilibrium blocking temperatures for magnesite of ∼490 °C. Our study demonstrates the applicability of the clumped isotope approach to provide information on the formation of magnesium carbonates as ore resources, surface records of climate, and metamorphic assemblages.
Gesehen am 20.03.2017